Um estudo de caso de implementação das boas práticas de fabricação em uma empresa de médio porte do setor farmacêutico – dificuldades e recomendações - Fiocchi, Carlos César; Miguel, Paulo Augusto Cauchick (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper aims at demonstrating the difficulties in the implementation of the Good Manufacturing Practices (GMP) standard in a medium-sized pharmaceutical company, according to the requirements. This work outlines the different quality assurance standards with emphasis on the GPM. The research strategy was based on a single-case study and the data collection involved document analysis and semi-structured interviews. Document records from self-assessments were verified and the company level and evolution were checked according to the standard. After the data collection, the analysis provided elements to answer the proposed research questions and confirm the evidences of the experienced difficulties to comply with the standard. The difficulties involved: a lack of more prepared labor, installations not designed according to the GMP, old equipment and an ineffective responsibility definition inside the organization. This paper concludes that, even with no full compliance with the standard, the company demonstrated to have minimal conditions to fulfill the standard, allowing for the manufacture of medicines. Keywords: Good Manufacturing Practices; Pharmaceutical Industry; Quality System.